Single-Cell Regulatory Network Inference and Clustering Identifies Cell-Type Specific Expression Pattern of Transcription Factors in Mouse Sciatic Nerve - Li, Mingchao; Min, Qing; Banton, Matthew C.; Dun, Xinpeng (Frontiers in Cellular Neuroscience, 2021)
Advances in single-cell RNA sequencing technologies and bioinformatics methods allow for both the identification of cell types in a complex tissue and the large scale gene expression profiling of various cell types in a mixture. In this report, we analysed a single-cell RNA sequencing dataset for the intact adult mouse sciatic nerve and examined cell type specific transcription factor expression and activity during peripheral nerve homeostasis. In total, we identified 238 transcription factors expressed in 9 different cell types of intact mouse sciatic nerve. Vascular smooth muscle cells have the lowest number of transcription factors expressed with 17 transcription factors identified. Myelinating Schwann cells have the highest number of transcription factors expressed with 61 transcription factors identified. We created a cell type specific expression map for the identified 238 transcription factors. Our results not only provide valuable information about the expression pattern of transcription factors in different cell types of adult peripheral nerves but also could facilitate future studies to understand the function of key transcription factors in peripheral nerve homeostasis and disease.